2021
DOI: 10.1111/jfbc.13861
|View full text |Cite
|
Sign up to set email alerts
|

Purple sweet potato extract maintains intestinal homeostasis and extend lifespan through increasing autophagy in female Drosophila melanogaster

Abstract: Purple sweet potatoes extract (PSPE) have been used as a natural food antioxidant with high anthocyanin concentrations. Research investigated the lifespan and the mechanisms of PSPE on female Drosophila melanogaster. Supplementation of PSPE extended the lifespan by 16.3% and had a protective effect on injury by oxidative stress. PSPE treatment enhanced the endogenous antioxidant enzyme activity and reduced malondialdehyde (MDA) content. Furthermore, PSPE significantly up‐regulated foxo‐related genes, inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…As shown in Figure 5c,d, the intestinal microflora was significantly reduced after administration of HE, and intestinal homeostasis was maintained. It is in line with Zhang, Wang, et al (2021), whose study reported that purple sweet potatoes extract, with high anthocyanin concentrations, could sustain intestinal homeostasis of D. melanogaster with aging. Moreover, aging and tissue damage led to abnormal proliferation and enhance terminal differentiation of ISCs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Figure 5c,d, the intestinal microflora was significantly reduced after administration of HE, and intestinal homeostasis was maintained. It is in line with Zhang, Wang, et al (2021), whose study reported that purple sweet potatoes extract, with high anthocyanin concentrations, could sustain intestinal homeostasis of D. melanogaster with aging. Moreover, aging and tissue damage led to abnormal proliferation and enhance terminal differentiation of ISCs.…”
Section: Discussionsupporting
confidence: 89%
“…The method of lifespan determination is based on the literature (Zhang, Wang, et al, 2021). Two‐day‐old D. melanogaster was divided into 4 groups, with 10 bottles in each group and 20 flies in each bottle.…”
Section: Methodsmentioning
confidence: 99%
“…Food intake was determined by referring to the method of previous studies [14] . Briefly, wild-type flies (n = 100 per group) were cultured for 4 days in diets with or without naringin or resveratrol, then placed in empty tubes for 2 h. The flies were moved to diets including 0.2% rhodamine B sulfonate sodium salt (Sigma, USA) for 3 h. A subjective rating scale ranging from 0 to 5 (colorless abdomen to completely red) was used to reflect the food intake.…”
Section: Food Intake and Body Weight Assaysmentioning
confidence: 99%
“…Due to their known antioxidative potential, the capacity of anthocyanins to delay aging or the progression of age-related diseases has therefore been explored [94,95]. For instance, purple sweet potato extracts, known to contain a high quantity of anthocyanins, have been investigated for their life-prolonging potential in Drosophila melanogaster [96]. In their research, NAME examined the effect of purified purple sweet potato extract on female wild-type D. melanogaster.…”
Section: Anthocyaninsmentioning
confidence: 99%